Usability Evaluation of Information Literacy Programmes: The Case Study of “Orion” - Garoufallou, Emmanouel; Dani, Anxhela; Chatzopoulou, Chrysanthi; Siatri, Rania; Virkus, Sirje; Mystakopoulos, Fotis; Antonopoulou, Stavroula (Communications in computer and information science, 2015)
This paper refers to an evaluation project conducted at the Alexander Technological Educational Institute of Thessaloniki during 2014. The project aimed to evaluate the information literacy programme Orion. Orion is a useful tool that constitutes a most vital part of the information literacy skills evolution. The project aimed to evaluate the usability of Orion, specifying whether or not the programme improves information literacy skills of students providing content and functionality excellence. Additionally, it is very important to measure the usability of the structure that the programme follows. The method applied was measuring effectiveness, efficiency, learnability, and satisfaction. Most users appeared to be positively inclined towards the service, but during task performance and as they became more acquainted with the system, they became more critical as they confronted difficulties; such as the terminology used in it.